Application of Monte Carlo simulation methods in risk management - Suhobokov, Alexander (Journal of Business Economics and Management, 2007)
The paper deals with Monte Carlo simulation method and its application in Risk Management. The author with the help of MATLAB 7.0 introduces new modification of Monte Carlo algorithm aimed at fast and effective calculation of financial organization’s Value at Risk (VaR) by the example of Parex Bank’s FOREX exposure. First Published Online: 14 Oct 2010